Automatic material grading and screening device - ZHOU MIN; PAN JIAFU (2023)
The utility model relates to the technical field of screening devices, and discloses an automatic material grading and screening device. The screening device comprises a screening box, a second movable baffle, a third movable baffle and a second filter screen, clamping grooves are formed in the second movable baffle and the third movable baffle, a first movable baffle is slidably connected into the clamping grooves of the second movable baffle and the third movable baffle, and a first filter screen is arranged in the first movable baffle. A second clamping groove is formed in the outer surface of the screening box and slidably connected with a connecting block, a special-shaped connecting rod is welded to the side, close to the screening box, of the connecting block, a hydraulic cylinder is welded to the inner side wall of the side, away from the screening box, of the special-shaped connecting rod, and an output shaft of the hydraulic cylinder is welded to the side, away from the screening box, of a first mov